Hypoxia-activated prodrugs and redox-responsive nanocarriers - Zeng Y (Dove Medical Press, 2018)
Yun Zeng,1,* Jingwen Ma,2,* Yonghua Zhan,1 Xinyi Xu,1 Qi Zeng,1 Jimin Liang,1 Xueli Chen1 1Engineering Research Center of Molecular and Neuro Imaging of the Ministry of Education, School of Life Science and Technology, Xidian University, Xi’an 710071, Shaanxi Province, People’s Republic of China; 2Department of Pharmaceutical Analysis, China Pharmaceutical University, Nanjing 210009, Jiangsu Province, People’s Republic of China *These authors contributed equally to this work Abstract: Hypoxia is one of the marked features of malignant tumors, which is associated with several adaptation changes in the microenvironment of tumor cells. Therefore, targeting tumor hypoxia is a research hotspot for cancer therapy. In this review, we summarize the developing chemotherapeutic drugs for targeting hypoxia, including quinones, nitroaromatic/nitroimidazole, N-oxides, and transition metal complexes. In addition, redox-responsive bonds, such as nitroimidazole groups, azo-groups, and disulfide bonds, are frequently used in drug delivery systems for targeting the redox environment of tumors. Both hypoxia-activated prodrugs and redox-responsive drug delivery nanocarriers have significant effects on targeting tumor hypoxia for cancer therapy. Hypoxia-activated prodrugs are commonly used in clinical trials with favorable prospects, while redox-responsive nanocarriers are currently at the experimental stage. Keywords: antitumor drugs, hypoxia, nanoparticles, redox-sensitive, tumor therapy